The Translation of Cyclin B1 and B2 is Differentially Regulated during Mouse Oocyte Reentry into the Meiotic Cell Cycle. Issue 1 (December 2017) - Han, Seung; Martins, João; Yang, Ye; Kang, Min; Daldello, Enrico; Conti, Marco
Abstract Control of protein turnover is critical for meiotic progression. Using RiboTag immunoprecipitation, RNA binding protein immunoprecipitation, and luciferase reporter assay, we investigated how rates of mRNA translation, protein synthesis and degradation contribute to the steady state level of Cyclin B1 and B2 in mouse oocytes. Ribosome loading ontoCcnb1 andMos mRNAs increases during cell cycle reentry, well after germinal vesicle breakdown (GVBD). This is followed by the translation of reporters containing 3′ untranslated region ofMos orCcnb1 and the accumulation of Mos and Cyclin B1 proteins. Conversely, ribosome loading ontoCcnb2 mRNA and Cyclin B2 protein level undergo minimal changes during meiotic reentry. Degradation rates of Cyclin B1 or B2 protein at the GV stage are comparable. The translational activation ofMos andCcnb1, but notCcnb2, mRNAs is dependent on the RNA binding protein CPEB1. Inhibition of Cdk1 activity, but not Aurora A kinase activity, prevents the translation ofMos orCcnb1 reporters, suggesting that MPF is required for their translation in mouse oocytes. Conversely, Ccnb2 translation is insensitive to Cdk1 inhibition. Thus, the poised state that allows rapid meiotic reentry in mouse GV oocytes may be determined by the differential translational control of two Cyclins.